(untitled) (International Journal of Biomedical Research, 2014)
Background: Diabetes is a metabolic syndrome which affects most of the organs of the body including the central nervous system.Diabetic retinopathy is one of the complication resulting from derangement of neurovascular coupling and altered cell signaling pathway.Visually evoked potentials have evolved as a sensitive tool for detecting the neuropathic changes even before the clinically evident disease. Objectives: To compare the latencies and amplitudes of visually evoked potentials i.e.N75, P100 and N145 in diabetic and normal individuals. Materials and methods: 20 Diabetic individuals with type II diabetes mellitus in the age group of 45-60 yrs were included in the study group .Control group consisted of 10 age and sex matched non-diabetic individuals.Diabetic individuals with documented fundoscopy changes were included in the study and diabetic individuals with type I diabetes mellitus were excluded from the study.Visually evoked potentials were recorded using Viking select neurodiagnostic system. Conclusions: P100 Latency is significantly prolonged in diabetic individuals when compared to control group suggesting that the processing of information by the visual cortex is slower in diabetics due to central neuropathy changes.